Astronomia no documento curricular para Goiás-ampliado: desafios e possibilidades para os anos iniciais do ensino fundamental - Fernandes, Victória Hévelyn Pires (2023)
This study aimed to examine the contents related to Astronomy present in the Curriculum Document for Goiás Expanded, using a qualitative approach through exploratory document analysis. Data were collected and organized through filing techniques, and qualitative and quantitative surveys, in addition to the creation of codes and spreadsheets, using Discursive Textual Analysis (ATD). During the first ATD movement, 12 initial categories were identified, based on the literature review. Three intermediate categories related to teacher education, didactic resources and techniques, and knowledge of Astronomy were developed from these categories. As a result, two final categories were identified: challenges and possibilities for astronomy education. During the second movement of the ATD, 30 initial categories were identified from the reading of 2,714 skills proposed in the Expanded DC-GO, of which 442 were related to Astronomy. These skills were organized into three intermediate categories: conceptual, procedural, and attitudinal, and two final categories: explicit and implicit contents of Astronomy. The results indicate that the contents of Astronomy are present in the reference curriculum documentation for the city of Goiânia. The analysis of the production in the area suggests that changes are necessary regarding the initial and continued formation of teachers who teach Astronomy.